2019
DOI: 10.1108/imefm-06-2017-0143
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between precious metals price and Islamic stock markets

Abstract: Purpose This study aims to analyze the presence of a long-term relationship between precious metal prices, such as for gold, silver, platinum and palladium, and Islamic stock markets of 32 different countries – 21 developed and 11 developing. In this study, the long-term relationship between the precious metal prices and the Islamic stock markets of countries grouped by the Morgan Stanley Capital Index (MSCI) according to their level of development was examined. In the economies included in the study, it is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…By contrast, Kumar (2014) pointed out that there are variative, positive, even negative dynamic correlations between stock and gold in the crisis period in India so that gold becomes a good portfolio diversification in India. Chkili (2016) and Tuna (2019) asserted that there is a low negative correlation between the stock market and gold so that gold can become a safe haven and effective portfolio diversification when there is an extreme stock movement on a crisis period. The result is in line with Choudhry et al (2015) the disappearance of gold as a safe haven during the global economic crisis makes gold is not worth it to minimize the risk of the portfolio during the crisis period.…”
Section: Dynamic Correlation Between Cspi and Usd/ Idr Exchange Rate mentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, Kumar (2014) pointed out that there are variative, positive, even negative dynamic correlations between stock and gold in the crisis period in India so that gold becomes a good portfolio diversification in India. Chkili (2016) and Tuna (2019) asserted that there is a low negative correlation between the stock market and gold so that gold can become a safe haven and effective portfolio diversification when there is an extreme stock movement on a crisis period. The result is in line with Choudhry et al (2015) the disappearance of gold as a safe haven during the global economic crisis makes gold is not worth it to minimize the risk of the portfolio during the crisis period.…”
Section: Dynamic Correlation Between Cspi and Usd/ Idr Exchange Rate mentioning
confidence: 99%
“…Gold is one of the precious metals that considered as a safe asset to be stored in the long-run period because it has good durability (Robiyanto, Wahyudi, & Pangestuti, 2017). It also can be an effective diversification tool within the portfolio to reduce the risks (Tuna, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Maghyereh et al ( 2019) have studied the correlations of Islamic securities with gold, and their results suggested relatively lower correlations, which means gold is a good tool for diversification for Islamic securities. Tuna (2019) has concluded that gold persists to be an effective diversification tool in both Islamic share markets, as well as in traditional stock markets. Beckmann et al (2015) adopted a novel approach to conduct their research; they included statistics from 18 countries and 5 regional indices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the existing literature, some of the researchers have utilized only gold prices (Arfaoui & Ben Rejeb, 2017;Shakil et al, 2018;Tuna, 2018) and others have utilized only oil prices (Lardic & Mignon, 2008;Sahu et al, 2014;Mollick & Nguyen, 2015;Wen et al, 2017;Abdel-Latif et al, 2018;Areli Bermudez Delgado et al, 2018;Pandey & Vipul, 2018;Kumar, 2019;A. Mouna, 2019;Narayan, 2019;Charfeddine & Barkat, 2020) in order to examine their linkages with stock market indexes.…”
Section: Research Gapsmentioning
confidence: 99%